Penerapan Nilai Karakter Peduli Sosial Pada Peserta Didik Kelas II di Sekolah Dasar - Chan, Faizal; Pamela, Issaura Sherly; Shinta, Septiana Lara; Yoana, Alusi; Mardayani, Dwi; Sari, Ryan Kurnia (Universitas Nusantara PGRI Kediri, 2019)
This study aims to describe the inculcation of social care character values ​​in students at the private elementary school Iqra Tuah Sakato Muara Bulian. This research is a qualitative descriptive study. The study conducted observations, interviews and documentation with research subjects, namely teachers and students. In this study, researchers will focus on how the mechanism of the inculcation of the value of social care characters in learning, what factors influence the social care character of students, and what are the impacts. Data analysis uses data reduction, data presentation and drawing conclusions. The results showed that the implementation of social care character education was carried out by the teacher giving an example in the form of a direct example, the teacher also gave a spontaneous planting rebuking students who were ignorant with their friends